1981
DOI: 10.1007/bf00252659
|View full text |Cite
|
Sign up to set email alerts
|

The priming effect of glucose on insulin secretion from isolated islets of Langerhans

Abstract: Summary. Biphasic insulin secretion from perifused rat islets of Langerhans was enhanced if islets had previously been stimulated with glucose 16.6 mmol/1. The priming effect of glucose was reduced if mannoheptulose (16.6 mmol/1), deuterium oxide (D20; 98% v/v) or adrenaline (10 ~tmol/l) was included in the medium during the initial stimulation period, or if Calcium was omitted. Glyceraldehyde (16.6 mmol/1) but not theophylline (5 mmol/1) could substitute for glucose during the initial stimulation and make isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
35
2

Year Published

1983
1983
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 17 publications
8
35
2
Order By: Relevance
“…As would be expected from previous observations that second phase response to glucose was less deranged [17], late insulin release is markedly stimulated during prolonged exposure (60 min) of Acomys islets to glyceraldehyde. Such findings as well as other observations from our group [2,5,7] and others [3,4,8,9] suggest that the mechanisms that control first and second phase insulin release are distinct and dissociable.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As would be expected from previous observations that second phase response to glucose was less deranged [17], late insulin release is markedly stimulated during prolonged exposure (60 min) of Acomys islets to glyceraldehyde. Such findings as well as other observations from our group [2,5,7] and others [3,4,8,9] suggest that the mechanisms that control first and second phase insulin release are distinct and dissociable.…”
Section: Discussionsupporting
confidence: 85%
“…Upon stimulation with glucose, normal islets exhibit biphasic dynamics of insulin release, representing the net expression of the interaction between several regulatory events, including time-dependent inhibitory and potentiating signals [1][2][3][4][5][6][7][8][9][10]. Limited information exists regarding the nature of these regulatory signals.…”
mentioning
confidence: 99%
“…We [1-4, 8, 10, 11] and others [5][6][7]9] have shown that many agents which stimulate the acute release of insulin also modify the responsiveness of the islet for a considerable time, resulting in either potentiation or inhibition of subsequent insulin responses. We have termed these effects time-dependent potentiation and inhibition (TDI), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, when glucose was added to the second arginine pulse only, the inhibition generated by the first arginine pulse did not express itself, insulin release remaining similar to control. We conclude that: (1) short stimulations of the pancreas by arginine or glucose generate long-lasting inhibition of the insulin response to subsequent stimulations; (2) synergistic amplification of the insulin response by addition of glucose to arginine obliterates the inhibition; (3) glucose does not suppress the induction of inhibition, it blocks the expression of the inhibitory signal on insulin secretion; (4) these in vitro findings are in keeping with observations in normal and hyperglycaemic man.Key words: Perfused pancreas, insulin secretion, arginine, synergism, time-dependent inhibition, time-dependent potentiation.Studies in vivo and in vitro have demonstrated that the insulin secretion rate is modified by prior sensitization of the pancreas to various insulin releasers [1][2][3][4][5][6][7][8][9][10]. While some stimulators like glucose may generate either a state of potentiation or inhibition in the islet according to the conditions of exposure [2,3,8], arginine induces only an inhibitory state [3,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation